2020
DOI: 10.1097/bor.0000000000000735
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis pathogenesis: contribution of recent advances in genetics

Abstract: Purpose of review To review susceptibility genes and how they could integrate in systemic sclerosis (SSc) pathophysiology providing insight and perspectives for innovative therapies. Recent findings SSc is a rare disease characterized by vasculopathy, dysregulated immunity and fibrosis. Genome-Wide association studies and ImmunoChip studies performed in recent years revealed associated genetic variants mainly localized in noncoding regions and mostly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 89 publications
1
20
0
Order By: Relevance
“…39 There was a close genetic linkage between A20 and SSc, as a number of cohort studies show that single nucleotide polymorphisms (SNPs) about A20 are closely related to the susceptibility of SSc, [41][42][43][44] and the genome-wide association studies and immunochip studies conducted in recent years have also confirmed that the gene variation of TNFAIP3 is related to SSc. 45 Another study observed the expression of A20 by culturing human skin fibroblasts in vitro. 46 This study also observed the effect of A20 overexpression or small interfering RNA (siRNA)-mediated A20 knockdown in human skin fibroblasts on the fibrotic responses induced by TGF-b.…”
Section: Discussionmentioning
confidence: 99%
“…39 There was a close genetic linkage between A20 and SSc, as a number of cohort studies show that single nucleotide polymorphisms (SNPs) about A20 are closely related to the susceptibility of SSc, [41][42][43][44] and the genome-wide association studies and immunochip studies conducted in recent years have also confirmed that the gene variation of TNFAIP3 is related to SSc. 45 Another study observed the expression of A20 by culturing human skin fibroblasts in vitro. 46 This study also observed the effect of A20 overexpression or small interfering RNA (siRNA)-mediated A20 knockdown in human skin fibroblasts on the fibrotic responses induced by TGF-b.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated GSDMs in autoimmune and inflammation-driven diseases. GSDMA mutants have been linked to limited cutaneous system sclerosis ( 33 , 34 ) and inflammatory bowel disease ( Table 1 ) ( 35 ). The results of transethnic meta-analysis of genome-wide associated studies involving Japanese and European populations with a total of 4,436 cases and 14,751 controls revealed that a missense mutation in GSDMA (rs3894194) is associated with system sclerosis.…”
Section: Implicated Diseases Associated With Gsdm Family Genesmentioning
confidence: 99%
“…Many studies have some evidence supporting the critical role of these signaling pathways and immune dysregulation in the pathogenesis of SSc ( 45 ). One study showed that stimulation of dendritic cells carrying this variant of SSc with a TLR2 agonist increased macrophage activation, resulting in increased production of interleukin-6 (IL-6) and tumor necrosis factor ( 46 ), thus participating in the pathogenesis of SSc.…”
Section: Discussionmentioning
confidence: 99%